GENETIC BREEDING OF MAIZE FOR HIGH LEVELS OF AMYLOSE AND AMYLOPECTIN IN THE GRAINS (REMUNOM, 2026)
This literature review explored maize genetic breeding to increase amylose and amylopectin content in maize grains. The composition of starch, divided between amylose and amylopectin, significantly affects animal performance and the quality of maize-derived products. The synthesis of amylose and amylopectin in maize, relating it to different mutant genes such as wx (for waxy starch) and ae (for high amylose content), was highlighted. The main genetic breeding strategies for these traits were discussed, such as backcrossing and self-fertilization, to develop lines with different concentrations of amylose and amylopectin. The influence of environmental factors on the expression of amylose and amylopectin in maize grains was also explored. Changes in temperature, humidity, and other meteorological conditions affect the amylose/amylopectin ratio and the molecular structure of grains. The importance of these studies for optimizing animal nutrition, improving food and feed production, and developing industrial products from maize was highlighted, emphasizing the potential of genetic breeding to address future challenges in agriculture and the food industry. Genetic breeding of maize for high amylose and amylopectin content promotes promising solutions for reducing costs, especially in animal protein production.